Cerebral perfusion and its association with serum endothelin-1 in multiple sclerosis. Issue 1 (31st December 2022) - Hammad, Azza Bayoumi; El Din, Eman Mohammed Seif; Abdel Azim, Ghada Saed; Abboud, Mohamed Ali
ABSTRACT: Multiple sclerosis (MS) is a chronic inflammatory, demyelinating and degenerative disease of the central nervous system. The exact pathogenesis of MS is incompletely understood. Cerebral vascular pathology is frequently verified in this disease. Perfusion studies may put light on the disease pathogenesis. In this study, we use dynamic susceptibility contrast-enhanced perfusion magnetic resonance imaging (DSC-MRI) to evaluate the cerebral perfusion in a group of MS patients. Thirty patients with relapsing–remitting multiple sclerosis (RRMS) and 20 healthy controls were investigated. The perfusion parameters were assessed for normal-appearing white matter (NAWM) and deep gray matter (DGM). Also, the serum level of the potent vasoconstrictor, endothelin-1(ET-1), was evaluated. There was reduction in cerebral perfusion in MS patients in comparison to healthy controls in the NAWM and (DGM). In addition, serum (ET-1) level was significantly elevated in the patient group and was correlated with the perfusion parameters. These findings suggest that cerebral hypoperfusion may play an important role in the pathogenesis of MS lesions. ET-1 has a role in cerebral hypoperfusion in both NAWM and DGM of RRMS patients. DSC-MRI could be an applicable objective measure to detect cerebral hemodynamic changes in MS.